Functional relationships between serum creatinine, creatine, urea and their purges in patients with lupus - Ramírez Velasco, Manuel (1962)
The observation of some patients suffering from systemic lupus erythematosus in which low numbers of creatinine was found despite having purges below normal, did I suspect that might affect the functional relationship between serum creatinine and its respective debugging. The presence of musculoskeletal syndromes francs in many patients with systemic lupus erythematosus, also justified the suspicion of a disorder of the metabolism of creatine cratinina.